Water use efficiency of coriander produced in a low-cost hydroponic system - José A. Santos Júnior; Hans R. Gheyi; Antônio R. Cavalcante; Salomão de S. Medeiros; Nildo da S. Dias; Delfran B. dos Santos (Revista Brasileira de Engenharia Agrícola e Ambiental)
ABSTRACT The increase of water use efficiency in crop production is a clear need in areas with restricted access to this resource and, in these cases, the adoption of forms of cultivation contextualized to local conditions are essential. Thus, the implications of the variation in the amount of seeds per cell (0.5, 1.0, 1.5 and 2.0 g) and spacing between cells (7.0, 10.0 and 15.0 cm) on variables related to consumption and water use efficiency for the production of coriander (cv. Tabocas) in a low-cost hydroponic system, an alternative for semiarid regions, were evaluated. A completely randomized experimental design, analysed in 4 x 3 factorial scheme with three replicates, was adopted, and the data were subjected to analysis of variance at 0.05 probability level. It was found that the reduction in the spacing between cells has a better cost-benefit ratio with respect to water consumption, biomass produced and cost of seeds. Therefore, it is recommended the adoption of a spacing of 7.0 cm between cells and the use of 1.0 g seeds per cell; this configuration promoted efficiency of 81.59 g L-1 in shoot green mass production and total mass of 62.4 g coriander bunches.